Penerapan Manajemen Kinerja Pegawai Pemerintah Kota X Antara Masa Normal dan Masa Pandemi - Nur Syuhada', Muhammad (Psyche 165 Journal, 2024)
The Covid 19 pandemic that occurred in Indonesia at the beginning of 2020 has been designated as a non-natural national disaster which creates a public health emergency, so preventive efforts are needed to overcome the pandemic. The implementation of work from home (WFH) is an effort to prevent the spread of the virus within City X government agencies. An initial study conducted by researcher found that the ASN performance management system in the X City Government during the implementation of WFH still feels ineffective due to the control system not being fulfilled and even some agency resources being deemed not ready to implement the WFH system. This research aim to analyze the work management of X City Government employees during normal times and the Covid-19 pandemic period or the period of adaptation to new habits. Researcher used a qualitative descriptive approach which aims to describe in depth the performance of X City Government Employees during the Normal and Pandemic periods. The main data collection tool was FGD with 30 representatives of several regional organizations in the X City government. In addition, researchers involved 433 ASN employees in X City to fill out a survey regarding performance during normal times, during the pandemic and during the adaptation to new habits. Data from FGDs and surveys were analyzed using simple qualitative and quantitative analysis with an interactive analysis model with steps of data collection, data reduction, data presentation and drawing conclusions. The results of the research found that the X City Government's ASN performance management during normal times had been implemented in accordance with work management principles, although there is a decrease compared to employee performance in normal times. Recommendation from the results of this research can be used as study material regarding the performance of X City Government employees during normal times and during the pandemic.